2013
DOI: 10.1249/mss.0b013e318285f57e
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Hemostatic Parameters of Interrupting Sitting with Intermittent Activity

Abstract: Uninterrupted sitting increased fibrinogen and reduced plasma volume, with associated increases in hemoglobin and hematocrit. Activity breaks attenuated these responses, indicative of an ameliorating influence on the procoagulant effects of uninterrupted sitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 31 publications
3
61
2
5
Order By: Relevance
“…Our results support findings from a recent experimental trial that demonstrated increases in plasma fibrinogen with prolonged uninterrupted sitting that was attenuated with active breaks. 41 Some epidemiological studies have demonstrated that associations between sedentary behaviour and CVD are attenuated in physically active participants. 14,15 However, in our analysis to explore the possible additive effects of physical activity and TV viewing on inflammatory markers we did not observe any significant effect modification of physical activity (see figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…Our results support findings from a recent experimental trial that demonstrated increases in plasma fibrinogen with prolonged uninterrupted sitting that was attenuated with active breaks. 41 Some epidemiological studies have demonstrated that associations between sedentary behaviour and CVD are attenuated in physically active participants. 14,15 However, in our analysis to explore the possible additive effects of physical activity and TV viewing on inflammatory markers we did not observe any significant effect modification of physical activity (see figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…As more experimental studies continue to emerge, it is becoming increasingly clear that there are likely to be multiple complex mechanisms and interacting pathways involved with cardiometabolic health. For instance, recent studies suggest that responses to sedentary behaviour may also be diet/energy intake related [39], or even linked to fibrinolytic factors [60] and skeletal muscle gene expression [61,62].…”
Section: Better Understand the Underlying Mechanistic Effects Of Sedementioning
confidence: 99%
“…Aunque comúnmente se ha considerado como una preocupación para la salud de los adultos mayores y aquellas personas que hacen viajes largos en avión, el estudio de caso de un varón de 32 años de edad, que pasaba demasiado tiempo en una estación de cómputo casi sin moverse, sacó a la luz el tema (Beasley, Raymond, Hill, Nowitz, & Hughes,2003). Algunas investigaciones experimentales posteriores lograron identificar cambios hematopoyéticos, así como la expresión de genes del músculo esquelético que podrían contribuir al desarrollo de una trombosis, como resultado de la inactividad física provocada por pasar demasiado tiempo sentado o por la simulación de pasar demasiado tiempo en esta posición (Howard et al 2013;Zderic and Hamilton 2012). La interrupción del tiempo sentado ante la estación de trabajo, con períodos de 2 minutos de caminata a unos 3.2 km/h tres veces por hora, logró reducir la aparición de factores sanguíneos que promueven la coagulación y el riesgo de trombosis (Howard et al 2013).…”
Section: Estaciones De Trabajounclassified
“…Algunas investigaciones experimentales posteriores lograron identificar cambios hematopoyéticos, así como la expresión de genes del músculo esquelético que podrían contribuir al desarrollo de una trombosis, como resultado de la inactividad física provocada por pasar demasiado tiempo sentado o por la simulación de pasar demasiado tiempo en esta posición (Howard et al 2013;Zderic and Hamilton 2012). La interrupción del tiempo sentado ante la estación de trabajo, con períodos de 2 minutos de caminata a unos 3.2 km/h tres veces por hora, logró reducir la aparición de factores sanguíneos que promueven la coagulación y el riesgo de trombosis (Howard et al 2013). Un estudio de caso individual y los análisis de tejidos de animales mostraron que las sesiones posteriores de actividad física no revierten la supresión de la lípido-fosfato-fosfatasa-1, sustancia que tendría un efecto protector al degradar los factores que promueven la trombosis (Zderic y Hamilton, 2012).…”
Section: Estaciones De Trabajounclassified